Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1074/jbc.m605860200
|View full text |Cite
|
Sign up to set email alerts
|

Identification in Archaea of a Novel D-Tyr-tRNATyr Deacylase

Abstract: Tyr deacylase. Instead, it displays homology with that of a bacterial peptidyl-tRNA hydrolase. We show, however, that the archaeal PAB2349 enzyme does not act against diacetyl-Lys-tRNA Lys , a model substrate of peptidyl-tRNA hydrolase. Based on the Protein Data Bank 1YQE structure, site-directed mutagenesis experiments were undertaken to remove zinc from the PAB2349 enzyme. Several residues involved in zinc binding and supporting the activity of the deacylase were identified. Taken together, these observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 26 publications
0
33
0
1
Order By: Relevance
“…Another type of d -Tyr-tRNA Tyr deacylase (DTD2) has been discovered in archaea (7). This enzyme displays the fold of a bacterial peptidyl-tRNA hydrolase and carries two firmly bound zinc ions, crucial to the activity (7).…”
Section: Introductionmentioning
confidence: 99%
“…Another type of d -Tyr-tRNA Tyr deacylase (DTD2) has been discovered in archaea (7). This enzyme displays the fold of a bacterial peptidyl-tRNA hydrolase and carries two firmly bound zinc ions, crucial to the activity (7).…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been observed that Escherichia coli and Bacillus subtilis tyrosyl-tRNA synthetases can potentially catalyze the formation of D-tyrosyl-tRNA Tyr to the same extent as with L-enantiomer (30). Interestingly, extracts of E. coli, yeast, rabbit reticulocytes, and rat liver were shown to have an enzyme activity capable of accelerating the hydrolysis of the ester linkage of D-Tyr-tRNA to release free tRNA and D-tyrosine (31). The fate of D-aminoacyl-tRNA had never been studied previously.…”
Section: Cell Death Detection Elisa Plus Assaymentioning
confidence: 99%
“…Unlike cyclodityrosine synthase, D-tyrosyl-tRNA deacylase is a nearly ubiquitous enzyme in bacteria, archaea, and eukaryotes [39,41,49]. Deletion of D-tyrosyl-tRNA deacylase from E. coli and S. cerevisiae results in the accumulation of D-aminoacyltRNAs, depleting the available pool of free tRNA and impairing cell growth [39,41].…”
Section: Discussionmentioning
confidence: 99%